Evaluation of API 20 STREP system for identifying Listeria species. Issue 5 (May 1989) - MacGowan, A P; Marshall, R J; Reeves, D S
Abstract : The API 20 STREP system was used to identify 146 known strains from seven species of the genus Listeria, including both pathogenic and environmental strains. The gallery was easy to use and tests, with the exception of leucine arylamidase (LAP) and starch fermentation (AMD), were simple to interpret. Identification to genus level was satisfactory but differentiation between species was poor. Using the API 20 STREP the haemolytic species L monocytogenes, seeligeri, and ivanovii could easily be differentiated from the non-haemolytic species L welshimeri, innocua, grayii and murrayi. Of the haemolytic species, L monocytogenes could not be distinguished from L seeligeri but L ivanovii could be separated from the two other haemolytic species because it fermented ribose. Non-haemolytic L welshimeri could not be differentiated from non-haemolytic L innocua, but mannitol and ribose fermenting non-haemolytic L grayi and L murrayi were easily differentiated from the other two non-haemolytic species. The API 20 STREP identified Listeria in four hours and therefore might be used for rapid identification of strains causing infection in man. It would, however, not be useful to identify environmental isolates when speciation is important.